IMPLEMENTATION OF STRATEGIC MANAGEMENT AT MTsN 1 TULUNGAGUNG - Zen Ma'arif, M.; Zaenul Fitri, Agus; Sulistyorini (International Journal of Multidisciplinary Reseach, 2025)
In the era of globalization and digitalization, educational institutions such as MTsN 1 Tulungagung face complex challenges arising from policy, technological, and social dimensions. To respond to these dynamics, the institution has implemented strategic management as a systematic approach to enhancing the effectiveness of resource management and the quality of education. This study aims to describe the process of implementing strategic management at MTsN 1 Tulungagung, identify supporting and inhibiting factors, and analyze its impact on improving educational quality. The research focuses on three main aspects: strategy implementation, encountered constraints, and their influence on institutional performance. This study employs a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed using the stages of data condensation, data display, and verification based on the Miles and Huberman model. The findings indicate that strategic management at MTsN 1 Tulungagung is carried out through four main stages: environmental analysis, strategy formulation, implementation, and evaluation and control. Key supporting factors include visionary leadership, teacher participation, and community support, while the main obstacles relate to limited resources and facilities. The implementation of strategic management has been shown to enhance teacher motivation, learning innovation, and school community participation; however, academic outcomes have not yet demonstrated significant improvement, as the strategic process is still in the strengthening phase